1996
DOI: 10.1016/0014-5793(96)00859-9
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Nef antigen of HIV‐1 is cytotoxic for human CD4+ T cells

Abstract: Key words: AIDS; HIV-1; Nef; CD4+ T cell; Cytotoxicity tion with nylon wool, and selective panning selection as described previously [16]. CD4+ T cells from lamina propria mononuclear cells (LPMCs) were a gift from Dr. M. Ito, Yamagata University School of Medicine. The T cells from PBMC and LPMC were cultured in Iscov's modified Dulbecco's medium (IMDM) containing 25 U/ml of rlL-2 and 10% heat-inactivated human AB serum (Gibco). Antibodies (Abs) and seraMouse monoclonal antibodies (mAbs), OKT-4 (anti-CD4) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
160
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(176 citation statements)
references
References 20 publications
14
160
1
Order By: Relevance
“…100 ng/ml, could be present in tissue compartments such as lymph nodes where macrophages and infected lymphocytes tightly interact (67,68). The low amounts of exogenous Nef detected in the serum of HIV-infected subjects could also result from the presence of immune complexes Nef-antiNef as reported previously (48).…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…100 ng/ml, could be present in tissue compartments such as lymph nodes where macrophages and infected lymphocytes tightly interact (67,68). The low amounts of exogenous Nef detected in the serum of HIV-infected subjects could also result from the presence of immune complexes Nef-antiNef as reported previously (48).…”
Section: Discussionsupporting
confidence: 64%
“…The amounts of exogenous Nef detected in the serum of HIV-infected subjects is around 10 ng/ml (48). At 10 ng/ml, we observed that recombinant Nef protein activates NF-kB, AP-1, and JNK (Figs.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…It was showed that majority of the nef protein was shown to be on the luminal side of these vesicles, although there was clearly nef protein on the vesicle surface as well. Nef has been shown to be secreted from infected cells and in one report nef was found to be secreted in association with small membrane-bound vesicles [19][20][21][22] . These identification was supported this study to analysis supernatant which may contains small membrane bounded vesicles contains nef protein.…”
Section: Purity Determination By Sds-page/western Blots Analysis Of Tmentioning
confidence: 99%